2019
DOI: 10.1007/s13592-018-0619-6
|View full text |Cite
|
Sign up to set email alerts
|

Automated classification of bees and hornet using acoustic analysis of their flight sounds

Abstract: To investigate how to accurately identify bee species using their sounds, we conducted acoustic analysis to identify three pollinating bee species (Apis mellifera , Bombus ardens , Tetralonia nipponensis ) and a hornet (Vespa simillima xanthoptera ) by their flight sounds. Sounds of the insects and their environment (background noises and birdsong) were recorded in the field. The use of fundamental frequency and mel-frequency cepstral coefficients to describe feature values of the sounds, and supported vector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 33 publications
(41 reference statements)
2
41
1
Order By: Relevance
“…The fusion of coefficients increases the efficiency and reliability of the system making the proposed approach unique in terms of insect species recognition. Compared to previous works, this proposal is capable of identifying and classifying 343 species of either katydids crickets or cicadas on the level of specific species with higher success rates than previous systems, as shown in [14][15][16][17][18].…”
Section: State Of the Artmentioning
confidence: 89%
See 1 more Smart Citation
“…The fusion of coefficients increases the efficiency and reliability of the system making the proposed approach unique in terms of insect species recognition. Compared to previous works, this proposal is capable of identifying and classifying 343 species of either katydids crickets or cicadas on the level of specific species with higher success rates than previous systems, as shown in [14][15][16][17][18].…”
Section: State Of the Artmentioning
confidence: 89%
“…The 57 mosquito recordings used in this work were labeled with a success rate of 92.2% detecting the presence or absence of mosquitoes surpassing human labelers. More recently, in [18], the authors identified three bee species and a hornet analyzing their flight sounds. The method was able to correctly distinguish between flight sounds and environmental sounds, but only had a precision of 70-90% in terms of species-specific identification.…”
Section: State Of the Artmentioning
confidence: 99%
“…Machine Learning techniques have demonstrated high efficiency and accuracy for classification of bumblebees and other groups of bees based on the characteristics of their buzzing-sounds [ 19 , 35 , 36 ]. Therefore, we chose some of the most common used ML classifiers to recognize the taxonomic identity of bees during visits to tomato flowers (according to S1 Table ): Logistic Regression [ 52 ], Support Vector Machines [ 53 , 54 ], Random Forest [ 55 ], Decision Trees [ 56 , 57 ], and a classifier ensemble [ 58 , 59 ]—a combination of multiple and diversified classifiers to generate a single classifier model.…”
Section: Methodsmentioning
confidence: 99%
“…These studies sought to differentiate the bee buzzing sounds from other sounds (cricket chirping and ambient noise) [ 31 ], recognize the presence of the queen in a beehive and detect an orphaned colony [ 32 , 33 ], or identify the circadian rhythm of a honeybee colony [ 34 ]. However, only three studies address the problem of automatic bee species classification, and these deal with twelve, two and four classes respectively [ 19 , 35 , 36 ]. Random Forest, Support Vector Machines, and Logistic Regression are the most applied classifiers, and Mel Frequency Cepstral Coefficients (MFCC) is the most used feature extraction strategy (see S1 Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Harmonic scanning radars can detect insects flying at low altitudes at a range of several hundred meters, but insects need to be tagged with a radar transponder and must be within line-ofsight (53,54). Collectively, the use of radar technology in entomology can provide valuable shown that even species classification can be done using machine learning on audio data, for example for birds (58), bats (61), grasshoppers (62), and bees (63). Although, it has been argued that the use of pseudo-acoustic optical sensors rather than actual acoustic sensors is a more promising technology because of the much improved signal-to-noise ratio in these systems, which may be a particularly important point for bioacoustics in entomology (64).…”
Section: Radar Acoustic and Other Solutions For In Situ Monitoringmentioning
confidence: 99%